1: Iqgap1 Signaling Promotes Foreign Body Response To Biomedical Implants. (July 2021) - Sivaraj, Dharshan; Padmanabhan, Jagannath; Henn, Dominic; Magbual, Noah J.; Andrikopoulos, Sophia L.; Chen, Kellen; Januszyk, Michael; Gurtner, Geoffrey C.
Abstract : Purpose: The longevity of biomedical implants is limited by adverse implant-tissue interactions leading to implant failure. In almost all cases, implant failure occurs due to a phenomenon known as the foreign body response (FBR). FBR is characterized by fibrous capsule formation around implanted devices, leading to implant malfunction as well as distortion of the surrounding tissue. In the context of breast implants, FBR leads to capsular contracture, which is the cause of a significant proportion of all breast implant failures. Despite the high prevalence of FBR-mediated implant failure, the underlying mechanisms of FBR are incompletely understood. Our work utilizing mass spectrometry has demonstrated that when compared to healthy subcutaneous tissue, foreign body capsules in mice and humans display an up-regulation of IQ Motif Containing GTPase Activating Protein 1 (IQGAP1), a scaffolding protein involved in multiple mechanotransduction pathways. Based on these findings, we sought to investigate which cellular subpopulations express IQGAP1 as well as its role in mechanotransduction pathways mediating the development of FBR. Methods: To verify the importance of IQGAP1-mediated signaling in FBR, we employed a murine model of mechanically stimulated silicone implants (MSI), which were implanted subcutaneously in wildtype (WT) and IQGAP1+/- haplo-insufficient mice to compare the effect of human levels of mechanical stress on FBR. Homozygous IQGAP1 KO mice have been previously reported to harbor a fragile phenotype, more prone to pulmonary vascular damage and gastric pathologies. Haplo-insufficient mice were utilized in these experiments in order to prevent potential systemic complications from elevated levels of mechanical stimulation produced by the MSI model. We explanted the foreign body capsules from IQGAP1+/- haplo-insufficient and WT mice and performed single-cell RNA sequencing (sc-RNA-seq) on cells isolated from the capsules. We histologically assessed the quantity as well as maturity of collagen deposition using Masson's Trichrome and Herovici staining of tissue sections from explanted foreign body capsules. Moreover, immunostaining for the mechanotransduction related proteins alpha-smooth muscle actin (α-SMA), phosphorylated focal adhesion kinase (p-FAK), phosphorylated cell division control protein 42 (p-cdc42), and phosphorylated extracellular signal-regulated kinase (p-ERK1/2) was performed to assess the impact of IQGAP1-deficiency on the protein level. Results: We found that IQGAP1-deficient mice displayed a significantly reduced FBR as evidenced by thinner capsules, lower levels of collagen deposition, collagen maturity, and myofibroblast activation. Our scRNA-seq analysis revealed a depletion of mechanoresponsive myeloid cells in IQGAP1-deficient mice. This was confirmed on the protein level by a significantly reduced expression of a-SMA, p-FAK, p-cdc42, and p-ERK1/2 in foreign body capsule tissue from IQGAP1-deficient mice compared to WT mice. Conclusion: Our results highlight the important role of IQGAP1 as a critical early stage mediator of mechanotransduction pathways contributing to the development of FBR. Further, we show that IQGAP1 plays a role in modulating the innate immune response to synthetic implants. Therefore, IQGAP1 may be a promising target for the development of novel therapeutics to limit the development of FBR around biomedical implants.